Stigma Exile in Surat Dari Praha Movie - Kartika Mulya Putri; Dr. Hapsari Dwiningtyas, S.Sos, MA (Interaksi Online, 2016)
Film as a form of mass media is able to convey the message to the audience. Film is a representation that produce reality was constructed to provide an overview through the code, myths, ideologies of the culture. Surat Dari Praha is a film that describe the life of Indonesian exiles become who victims of events in Indonesia in 1965, especially regarding the stigma attached to their identity. The purpose of this research is describe how stigma exiles presented through visual symbols and linguistics as well as reveal the ideology that is in Surat Dari Praha. The theory used in this research is the theory of representations of Stuart Hall in the critical paradigm. The researcher used qualitative approach and John Fiske semiotic analysis to examine and analyze the symbol in Surat Dari Praha. There are three levels which described by Fiske, there are reality level, representation and ideology. The results showed that, found stigma exiles shown by the level of reality by visualization through appearance, fashion, make-up, setting, environment, style of speech and expression. While the level of technical representation, explain the details of the exile stigma seen through aspects of the camera, lighting, sound, narration, characters and characterizations. The ideology is shown passing through the Surat Dari Praha that presents exile as people who hold long-distance nationalism.